PURWARUPA PERANGKAT DETEKSI DINI BANJIR BERBASIS INTERNET of THINGS - Fuad Dwi Hanggara; Rama Dani Eka Putra (LPPM STMIK Lombok, 2021)
Floods are still the focus of attention because floods even cause many losses and casualties. A flood occurs due to the overflowing of water from the maximum limit of the water flow storage. Therefore early detection of the water level is required. This study aims to monitor water levels online as early information on floods. This supervision uses an Internet of Things (IoT) technology approach so that water level information can be known in real-time. The HC-SR 04 Ultrasonic Sensor is used as a water level reader, and the Arduino UNO R3 as a catcher processor then sends data wirelessly to the Thingspeak application so that it can be read from both smartphones and websites. The results of this study are a water level detection device that can inform what height. Safe or dangerous and can provide the notification. Thus this detection system can be used for early information on the occurrence of flooding